Height Estimation of a Blimp Unmanned Aerial Vehicle Using Inertial Measurement Unit and Infrared Camera - Villeneuve, Hubert (Université d'Ottawa / University of Ottawa, 2017)
Increasing demands in areas such as security, surveillance, search and rescue, and communication, has promoted the research and development of unmanned aerial vehicles (UAVs) as such technologies can replace manned flights in dangerous or unfavorable conditions. Lighter-than-air UAVs such as blimps can carry higher payloads and can stay longer in the air compared to typical heavier-than-air UAVs such as aeroplanes or quadrotors. One purpose of this thesis is to develop a sensor suite basis for estimating the position and orientation of a blimp UAV in development with respect to a reference point for safer landing procedures using minimal on-board sensors. While the existing low-cost sensor package, including inertial measurement unit (IMU) and Global Navigation System (GPS) module, could be sufficient to estimate the pose of the blimp to a certain extent, the GPS module is not as precise in the short term, especially for altitude. The proposed system combines GPS and inertial data with information from a grounded infrared (IR) camera. Image frames are processed to identify three IR LEDs located on the UAV and each LED coordinate is estimated using a Perspective-n-Point (PnP) algorithm. Then the results from the PnP algorithm are fused with the GPS, accelerometer and gyroscope measurements using an Extended Kalman Filter (EKF) to get a more accurate estimate of the position and the orientation. Tests were conducted on a simulated blimp using the experimental avionics.
Keywords: Blimp; UAV; IR camera; IMU; GPS; Pose estimation; EKF